2018
DOI: 10.1016/j.joco.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab as rescue therapy following treatment failure with laser photocoagulation in retinopathy of prematurity

Abstract: PurposeTo evaluate the efficacy of intravitreal bevacizumab (IVB) in case of treatment failure with laser photocoagulation in retinopathy of prematurity (ROP).MethodsA retrospective review of infants treated with IVB injection due to treatment failure with laser photocoagulation was performed. The anatomical results and complications were evaluated after treatment.Results9 eyes of 6 premature infants with a mean gestational age of 26.8 ± 3.0 weeks (range, 23–32 w) and mean birth weight of 958 ± 319 g (range, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Anti-VEGF agents are frequently used together with laser photocoagulation in the treatment of APROP (26). In some studies, anti-VEGF injection is recommended as rescue therapy in cases of laser photocoagulation failure (27). However, in a small number of series, it was shown that laser photocoagulation can be used if the disease progresses after IVI (28).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-VEGF agents are frequently used together with laser photocoagulation in the treatment of APROP (26). In some studies, anti-VEGF injection is recommended as rescue therapy in cases of laser photocoagulation failure (27). However, in a small number of series, it was shown that laser photocoagulation can be used if the disease progresses after IVI (28).…”
Section: Discussionmentioning
confidence: 99%
“…15 Further, laser therapy may be required in the case of contraindications to anti-VEGF, such as conjunctivitis or external eye infections. 90 Contraindications to using intravitreal anti-VEGF include ocular or periocular infections and severe intraocular inflammation. 47 Figure 1 represents a case study where bevacizumab is followed by laser therapy.…”
Section: Few Clinical Scenarios For Rop Managementmentioning
confidence: 99%
“…This understanding forms the basis for our current therapeutic interventions, which are aimed at amelioration of neovascularization in the second phase of ROP. These include ablation of avascular retinal tissues, now done with laser, or reduction in expression of the proangiogenic growth factor VEGF and can be administered as a monotherapy or as sequential therapy [29][30][31].…”
Section: Rop Molecular Pathogenesis Informs Current Rop Interventionsmentioning
confidence: 99%